TM Cellular Sdn Bhd's sales performance: a case study of its corporate and government customers in Kuching/ Ahmad Pahmi Ibrahim ... [et al.] - Ibrahim, Ahmad Pahmi; Eali, Daud; Ason, Augustine; Bunchol, Roneo Joseph; Safahan, Sindy Azlina; Jimbau, Wilfred Bertson (2004)
The sales performance of TM Cellular Sdn Bhd has not been constant in the past three years. This trend has been attributable to various factors including the pattern of usage of cellular services and response of the company’s various customers for the company’s products and services. The corporate and government customers are one of the company’s major customers and they too contribute to the sales trend.